Herpes Simplex Virus 1 encephalitis with normal cerebrospinal fluid after brain radiotherapy in a patient with glioblastoma. A case report and review of literature - Mutti, Carlotta; Curti, Erica; Ciliento, Rosario; Melpignano, Andrea; Florindo, Irene; Zinno, Lucia; Sasso, Enrico; Parrino, Liborio; Pavesi, Giovanni; Vaudano, Anna Elisabetta (Acta Biomedica Atenei Parmensis, 2019)
Herpes simplex virus encephalitis (HSE) is the most common cause of letal encephalitis and its prevalence appears higher among oncologic patients who undergo brain radiotherapy (RT). We describe a case of 76-year-old woman with glioblastoma multiforme (GBM) who developed HSE shortly after brain RT. Cerebrospinal fluid analysis (CSF) was normal and the diagnosis was driven by brain MRI and EEG. Prompt introduction of antiviral therapy improved the clinical picture. We highlight the importance of EEG and brain MRI for the diagnosis and suggest the possibility of antiviral profilaxys in oncologic patients who undergo brain RT.